PERANCANGAN BALAI PENELITIAN SAYURAN ORGANIK DENGAN PENERAPAN ARSITEKTUR RAMAH LINGKUNGAN DI KECAMATAN CIJERUK KABUPATEN BOGOR - Siradj, Muhammad; Iskandaria, Harfa; Suryandari, Putri (MAESTRO, 2020)
The Organic Vegetables Research Center is a place that is used to observe, analyze, develop and expand scientific insights as well as to discover new facts that exist in organic vegetable plants. The results of this study in the form of vegetable seedlings planted in the cultivation area. This vegetable research study aims to improve the quality of vegetables in the community so that vegetables consumed by the community have high nutrition and to be able to compete with the quality of vegetables imported from abroad. Environmentally Friendly Architecture in its application in the area of ​​the Organic Vegetables Research Center is to minimize the use of electrical energy that comes from PLN and is replaced by utilizing Natural Resources, namely the sun and wind which are channeled through Solar Panels and Wind Turbines. Then maximize the air and sunlight that enters the building and the use of environmentally friendly materials in each building.